A educação física numa escola de tempo integral (2005-2015): uma história possível - Muniz, Victor Hugo Regozino (2024)
This research was carried out using the historical method and had the years 2005 to 2015 as a time frame. The spatial frame fell on the municipality of Goiânia, specifically the Capuava neighborhood. The problem that led the research was how the full-time shift was implemented in this institution and how the Physical Education curricular component was inserted in this process. The specific objectives were I) reconstitute the full-time implementation process at the Moisés Santana Municipal School and the interfaces with the Physical Education curricular component; II) identify and analyze the role of Physical Education in building/recovering the Institution's credibility in the community; and III) Produce a Literary Short Story. To this end, the imperatives of cultural history in terms of dimension were used. The predominance was Oral History and the thematic domain fell on the History of Institutions. Discourse analysis was used to analyze and interpret the sources. In curricular terms, the municipal network of Goiânia, during the time frame of this research, used the Human Training and Development Cycles that were based on the Historical-Cultural theory over time, the document was updated and began to adopt the Critical-Overcoming approach as a guideline for the Physical Education curricular component. Thus, showing an alignment with scientific advances in the area. We suggest that teachers working in full-time schools use contributions from a cultural perspective of Physical Education. Regarding the Moisés Santana Municipal School, its entire transformation occurred through a great collective effort on the part of the school community, which still generates impacts on the institution today. Furthermore, Physical Education, together with other workshops, contributed to expanding the students' cultural repertoire and improving the institution's image in the community. Another important factor in changing the school was the intensification of control mechanisms, both in relation to staff and students, notably over the body.